Pre-paradigmatic status of industrial sustainability: a systematic review - Smart, Palie; Hemel, Stefan; Lettice, Fiona; Adams, Richard; Evans, Stephen (Emerald, 2017)
Purpose The purpose of this paper is to progress operations management theory and practice by organising contributions to knowledge production, in industrial sustainability, from disparate researcher communities. It addresses the principal question “What scholarly dialogues can be explicated in the emerging research field of industrial sustainability?” and sub-questions: what are the descriptive characteristics of the evidence base? and what thematic lines of scientific inquiry underpin the body of knowledge? Design/methodology/approach Using an evidenced-based approach, a systematic review (SR) of 574 articles from 62 peer-reviewed scientific journals associated with industrial sustainability is conducted. Findings This paper distinguishes three prevailing dialogues in the field of industrial sustainability, and uses Kuhn’s theory of paradigms to propose its pre-paradigmatic scientific status. The three dialogues: “productivity and innovation”, “corporate citizenship” and “economic resilience” are conjectured to privilege efficiency strategies as a mode of incremental reductionism. Industrial sustainability espouses the grand vision of a generative, restorative and net positive economy, and calls for a future research trajectory to address institutional and systemic issues regarding scaling-up and transition, through transformative strategies. Research limitations/implications The review is limited by the nature of the inquiries addressed in the literatures by specific researcher communities between 1992 and 2014. Originality/value This study performs the first SR in the field of industrial sustainability, synthesises prevailing scholarly dialogues and provides an evaluation of the scientific status of the field.
Keywords: Systematic review; Circular economy; Industrial sustainability; Sustainability-oriented innovation; System innovation